2018
DOI: 10.1371/journal.pone.0200498
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of the cobas Liat and Cepheid GeneXpert systems for Clostridium difficile detection

Abstract: Clostridium difficile infection (CDI) is a high burden and significant cause of healthcare-acquired infectious diarrhea in the United States (US). Timely and accurate diagnosis of CDI enables the rapid initiation of antibiotic therapy and infection control policies to minimize disease transmission. Polymerase chain reaction (PCR) assays have become a preferred modality for diagnosing CDI in the US. The cobas Liat Cdiff PCR test is a novel assay that can be performed on-demand for hospital-based testing with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A prospective comparison between the Liat and Xpert C. difficile/Epi test on fresh samples in the US population found 94.5% and 98.0% positive and negative percent agreement (13). A second prospective study in the U.S. population using the cobas 4800 Cdiff as the reference yielded 95.4% and 99.4% PPA and NPA, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective comparison between the Liat and Xpert C. difficile/Epi test on fresh samples in the US population found 94.5% and 98.0% positive and negative percent agreement (13). A second prospective study in the U.S. population using the cobas 4800 Cdiff as the reference yielded 95.4% and 99.4% PPA and NPA, respectively (11).…”
Section: Discussionmentioning
confidence: 99%
“…ese assays are based on integrated systems and do not require the separate nucleic acid extraction step. Several comparative studies with culture and other molecular methods showed these assays to have good correlation and sensitivities and specificities [25][26][27][28]. e remaining three assays, ARIES C. difficile (Luminex, Austin, TX, USA), GeneXpert C. difficile/Epi (Cepheid, Sunnyvale, CA, USA), and Verigene C. difficile (Luminex, Austin, TX, USA), use real-time PCR-based ARIES system, GeneXpert multiplex PCR system, and nanoparticle array hybridization-based Verigene equipment, respectively ( Table 1).…”
Section: Molecular Tests For the Detection Of Toxigenic Clostridioidementioning
confidence: 99%
“…Several independent studies have been performed on the evaluation of these assays and have sensitivities and specificities in the range of upper 90s [25,26,28]. All of these assays target C. difficile tcdB gene, while GeneXpert C. difficile and Verigene C. difficile assays can also detect hypervirulent ribotype 027 (BI/NAP1/027) strain of C. difficile by targeting the regulatory tcdC gene in which there is a deletion of nucleotide at position number 117 (Δ117tcdC) [25,26,28,29]. Besides, there are several CE-IVD and inhouse assays available for the detection of C. difficile genes ( Table 1).…”
Section: Molecular Tests For the Detection Of Toxigenic Clostridioidementioning
confidence: 99%